Dielectric spectroscopy study of hydrogen treated lead zirconate titanate (Pb (Zr, Ti)O3). Issue 6 (1st March 2013) - Shafiei, A.; Troczynski, T.
Abstract Dielectric spectroscopy technique is used in this work to study the structural changes inside lead zirconate titanate (Pb (Zr, Ti)O3 or PZT) exposed to hydrogen for 24 h at 550 °C, at constant pressure p = 0.13 bar. The results show that even after hydrogen treatment, there are still spontaneous dipoles (TiO or ZrO) inside the PZT. However, the dielectric constant is only about half of that of the as‐received sample. After the hydrogen treatment, two relaxation peaks were observed in the dissipation factor curves. While the kinetics of one of the relaxation peaks obeys the classical Arrhenius law, the other peak shows a non‐monotonic relaxation kinetics. Possible reasons for the formation of these peaks have been discussed.